RITUXIMAB IN THE TREATMENT OF REFRACTORY PEMPHIGUS VULGARIS - Fernandes, Iolanda Conde; Sanches, Madalena; Velho, Glória; Selores, Manuela (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
Pemphigus vulgaris is a rare autoimmune blistering disease affecting the skin and mucous membranes. In general, it has a severe course and may require long-term treatment with systemic corticosteroids and other immuno- suppressive drugs, which can lead to serious adverse events. Rituximab is a chimeric monoclonal antibody that targets the CD20 antigen found on B cells. Recently, there have been some reports documenting its use in the treatment of re- fractory pemphigus. The authors describe two clinical cases of pemphigus vulgaris refractory to conventional therapies that have been treated with rituximab and have achieved complete remission. In conclusion, our experience shows that rituximab is a valuable and safe option to treat severe and refractory pemphigus vulgaris KEYWORDS – Antibodies, monoclonal; Pemphigus.